Improve Vo2max And Arm Strength Of Handball Athletes - Yopi Hutomo Bhakti; Adi S (Universitas Negeri Semarang, 2022)
This study aims to increase Vo2Max and hand strength of handball athletes. This research is a pretest and posttest experimental research. The population in this study was the men's handball team of Lampung Province, totaling 18 athlete. The sample in this study used total sampling. The data obtained were then analyzed using SPSS (Version 21) to assess differences in physical conditions before and after treatment. The significant level at 0.05. High intensity interval training (HIIT) & Sprint Interval Training (SIT) workouts significantly increase VO2Max endurance. Body weight training exercises significantly increase hand strength endurance. The coach has to pay attention to two things: first, whether the measurement test is by the characteristics of the handball. Second, the athlete's performance in this research must improve by the treatment. There needs to be a particular measurement test instrument for handball athletes. Various treatments to improve athlete performance need to study in much literature.